Roman Imports, Imitations, and Local Identity in Sphakia, Southwest Crete - E. Francis, Jane (Rei Cretariae Romanae Fautorum Acta, 2015)
A considerable part of Roman material culture was dominated by the copy or replica. Part of this was no doubt due to the scale of the Empire, which necessitated the repetition of forms and objects in order to make them available to a largescale population, but the concept of reproducing or borrowing themes, styles, and compositions from pre-existing models also seems to have been an early and consistent feature of the Roman mindset. Replicas and reproductions can be observed in nearly all aspects of Roman life, from the decorative arts like sculpture and painting, to public symbols of influence and conquest, to objects of personal, daily use like silver and pottery.